MEMANFAATKAN HERMENETIKA DALAM PENELITIAN PSIKOLOGI - Diponegoro, Ahmad Muhammad (HUMANITAS (Jurnal Psikologi Indonesia), 2007)
AbstractInterest is growing in the hermeneutic to the study of human conduct. Hermeneuticphenomenology is offered as an approach to study interpreters that enables the study of  thenomenathat are difficult to address using a science based in rationalism or empiricism. Heideggerianconcepts that serve as the foundation of  a hermeneutic phenomenology of  interpreters are thathumans are situtated in their worlds, constituted by their worlds, enganged in everyday activity,and moved by their concerns in day-to-day life.This article explains the meaning of  the the wordhermeneutics and its usage in religion and psychology. This article also draws upon the work ofMartin Heidegger to put into practice  In the process, the three modes of  engagement distinguishedby Heidegger are described: the ready-to-hand, the unready-to-hand, and the present-at-hand